2004
DOI: 10.3109/s10165-004-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in patients with systemic lupus erythematosus and correlation of valvular lesions with anti-Ro/SS-A and anti-La/SS-B antibody levels

Abstract: The aim of this study was to evaluate the incidence of morphologic and functional cardiac abnormalities in patients with systemic lupus erythematosus (SLE) and to correlate the findings with levels of anti-Ro/SS-A, anti-La/SS-B, and anti-cardiolipin antibody (aCL). Sixty-two patients with SLE were enrolled in this study. All patients underwent complete history taking, clinical assessment, and standard two-dimensional and Doppler echocardiography. Anti-Ro/SS-A, anti-La/SS-B, and aCL levels were measured using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous reports have demonstrated that anti-Ro antibody was associated with subacute cutaneous lupus 24 , photosensitivity 25 , neonatal lupus heart block 26 , and valvular heart disease 27 . Actually, the effect of anti-Ro antibody positivity on renal manifestation in patients with SLE is not well known.…”
Section: Rheumatologymentioning
confidence: 98%
“…Previous reports have demonstrated that anti-Ro antibody was associated with subacute cutaneous lupus 24 , photosensitivity 25 , neonatal lupus heart block 26 , and valvular heart disease 27 . Actually, the effect of anti-Ro antibody positivity on renal manifestation in patients with SLE is not well known.…”
Section: Rheumatologymentioning
confidence: 98%
“…Compared to previous meta-analyses on this topic, the present study has significantly increased the sample size [ 38 , 39 ]. Additionally, the included studies demonstrate greater homogeneity in outcomes, and this represents the first meta-analysis to investigate the association between aβ2GPI and valvulopathy [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac diseases in lupus may involve the endocardium, myocardium, and pericardium and may be responsible for fatal outcome [11, 12]. Some cardiovascular abnormalities are seen with positive anti Ro/SS-A, anti La/SS-B, anti-cardiolipin (aCL), and anti-double-stranded DNA (anti-dsDNA) [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac diseases in lupus may involve the endocardium, myocardium, and pericardium and may be responsible for fatal outcome [11, 12]. Some cardiovascular abnormalities are seen with positive anti Ro/SS-A, anti La/SS-B, anti-cardiolipin (aCL), and anti-double-stranded DNA (anti-dsDNA) [1214]. However, most of these antibodies have not yet fully explained the pathogenic mechanisms of different SLE cardiac features including different valvular affection [12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation